LEADERSHIP AND MANAGEMENT IN PUBLIC ADMINISTRATION - Zubek, Michał (Edukacja Ekonomistów i Menedżerów, 2020)
All the organizations of the contemporary society require professional management. Special challenges are to be faced by public organizations which – because of their public mission – are obliged to take care of the common good. Proper management of public sector organizations by leaders with leadership qualities determine the level of public value attained by the very organizations. In the era of knowledge-based society, the rudimentary role of leadership is to achieve high standards by the organizations in the area of knowledge acquisition, knowledge sharing, implementation of innovative solutions and the ability to adapt to fast changing environment. Leadership is also about creating corporate cultural identity – a significant link between corporate mission and its human resources so as to develop the best possible standards of providing public services to inhabitants of the set community.